Analysis of the Impact of Key Macroeconomic Variables on Stock Market Development in Nigeria - Yusuf, Aminu; Gwadabe , Mohammed; Yahaya Ukashatu, Ali (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The study investigates the impact of key macroeconomic variables on stock development in Nigeria. The macroeconomic variables investigated include money supply, inflation, interest rate, exchange rate, trade openness, and all share index from 1986 to 2019. The Augmented Dickey-Fuller and Phillips-Perron and autoregressive distributive lag (ARD) model. Based on the findings, the long-run relationship indicates that money supply has a positive and statistically significant impact on all share indices. Furthermore, the exchange rate has positive but statistically insignificant effects on all share indices. The interest rate indicates positive and statistically significant effects on all share indices. Trade openness indicates a positive but statistically insignificant effect on all share indexes in Nigeria. The inflation rate shows a negative and statistically insignificant effect on all share indices in Nigeria. Interestingly, the error correction term (ECT) met all its theoretical and statistical requirements in both sign and size. It measures the speed of adjustment towards equilibrium after the initial deviation is corrected. The ECT coefficient is -0.201711 and significant at 5%, which indicates that 20 % of the disequilibrium due to the shock in the previous years is adjusted back to the long-run equilibrium in the current year. Based on the findings, the current study recommends that regulatory authorities and policymakers should ensure general stability in money supply and exchange rates by promoting trade in the economy.